Anisotropic conductive adhesive for micro joining in semiconductor interconnects application (solder alternative for fine pitch & environment friendly IC packaging) - Goh, Chin Foo (2008)
Microelectronic packaging has been accelerating towards adoption of novel solutions that offer lower cost, higher electrical performance, and better reliability. Flip chip technology lends itself excellently to these goals. The development of anisotropic and isotropic conductive adhesives (ACA & ICA respectively) as an alternative to solder bumps has received extensive attention in flip chip packaging as it offers an array of advantages like finer pitch interconnects, green processes, low cost, and low temperature processing. The Anisotropic Conductive Adhesive (ACA) is one promising candidate which also shows potential for future pitch reduction. However, the main concern with anisotropic conductive adhesive interconnection is its long-term reliability. The degree of spread of the conductive particles between the 50?m bump pitch and substrate pad, determined by the amount of pressure applied during the bonding process, has a great influence on the contact resistance of the ACA joints. As a result, nanosized conductive particles are preferably to use in the finer pitch ACA application (5?m bump pitch) to enhance reliability and performance. Therefore, the main objectives of this project are to develop nanosized hollow silica microspheres and encapsulate nickel with these microspheres. By using these encapsulated nickel particles as fillers in ACA interconnection, long-term reliability of ACA joints can be improved.